La forma hexagonal regular de las células de las abejas como solución de algunos problemas de óptimo - Muntean, Ioan (1996)
Wax compression and honeycomb resistance, and some other hypothesis as well (elimination of empty spaces between cylindrical cells and approximate emulation of bees bodies) drive to the first optimization problem: among all polygons with n ≥ 3 sides circumscribed into a circle with a given radius, determine the polygon P ∗ n with the smallest perimeter. This extrema problem with an isogonal condition is solved with a Lagrange multipliers method. It is proven that P ∗ n is a regular polygon and n ∈ {3, 4, 6}. Finally, another minimum problem drives to n = 6.